2015
DOI: 10.7341/20151116
|View full text |Cite
|
Sign up to set email alerts
|

Developing Innovative Business Models in Social Ventures

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…The second focus concerns "latent" or impact of SE legitimacy (Jokela and Elo 2015;Holt and Littlewood 2015;Nicolopoulou et al 2015) where they see SE legitimation to has its roots in the opportunity recognition process, which predominantly focus on the market in which the opportunity will be exploited (Stam, Arzlanian, and Elfring 2014). This view highlights their legitimisation and opportunity development (Hormiga, Batista-Canino, and Sanchez-Medina 2011) that emphasises on the importance of organisational cultural alignment with market needs in providing social value (Ruebottom 2013) and also its potential impact through their value creation activities (Holt and Littlewood 2015).…”
Section: Social Enterprise Legitimacymentioning
confidence: 99%
“…The second focus concerns "latent" or impact of SE legitimacy (Jokela and Elo 2015;Holt and Littlewood 2015;Nicolopoulou et al 2015) where they see SE legitimation to has its roots in the opportunity recognition process, which predominantly focus on the market in which the opportunity will be exploited (Stam, Arzlanian, and Elfring 2014). This view highlights their legitimisation and opportunity development (Hormiga, Batista-Canino, and Sanchez-Medina 2011) that emphasises on the importance of organisational cultural alignment with market needs in providing social value (Ruebottom 2013) and also its potential impact through their value creation activities (Holt and Littlewood 2015).…”
Section: Social Enterprise Legitimacymentioning
confidence: 99%
“…The selection criteria were as follows: 1) It was assumed to focus on social initiatives. Social initiatives were defined as social ventures representing "a new type of organization that aim to create sustainable social value, such as promoting the well-being of communities and their existence is based on developing solutions to tackle complex social problems" (Jokela & Elo, 2015). 2) To become case studies, selected initiatives should meet the sharing economy criteria according to Botsman (Collaborative Consumption, 2014) who defined sharing economy as "an economy built on a series of networks of connected individuals and communities versus centralized institutions, transforming how we can produce, consume, finance, and learn."…”
Section: Methodsmentioning
confidence: 99%
“…Results of the search of articles that define SE shows that the publication dates range from 2000 (Fowler, 2000) and 2015 (Jokela and Elo, 2015). Table 2 shows the 45 articles published in 31 academic journals.…”
Section: Distribution Of the Articles By Publication Outletmentioning
confidence: 99%
“…Continuing, analysing memes, we found that SE can occur in entities such as "small units" in large organizations as well as in a single chapter in "federations" . Other entities found in the subcategory "business" were memes related to "venture" and "social venture", scholars have used these terms to refer to the type of entity that is created in SE (Jokela and Elo, 2015;Meyskens, Robb-Post, Stamp, Carsrud, and Reynolds, 2010;Peredo and McLean, 2006). These scholars highlighted that these entities are created to fulfil a social mission.…”
Section: Category 3: Types Of Entities 4 In Sementioning
confidence: 99%